2015
DOI: 10.1002/celc.201500173
|View full text |Cite
|
Sign up to set email alerts
|

A Platinum–Vanadium Nitride/Porous Graphitic Nanocarbon Composite as an Excellent Catalyst for the Oxygen Reduction Reaction

Abstract: The oxygen reduction reaction (ORR) is a crucial process not only in fuel cells, but also in metal–air batteries, thus its electrocatalysts have attracted considerable attention. Here, we report the use of a vanadium nitride/porous graphitic nanocarbon (VN/PGNC) composite as an efficient support for a platinum electrocatalyst towards ORR. The VN/PGNC composite was synthesized through a gel‐coordination pyrolytic route. The gelatinous precursor formed by the coordination of VO3−, Ni2+, tetraethyl orthosilicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…[14][15][16] It hasb een proven that tungsten and tungsten nitride are effective co-catalysts of Pt and Pd in hydrogen evolution reactiona nd oxygen reduction reaction. [15,17,18] Importantly,i no ur previous work it was found that Mo 2 Nc ould distinctively enhancet he activity and selectivity of Pt on the ternary Pt-Mo 2 N/SBA-15 catalystf or the hydrogenation of CAL at the C=Ob ond to COL. Thus, we were curious to investigate whether the synergistic effect between Pd and WN could promote the catalytic performance of Pd for the hydrogenationo fc innamaldehyde at the C=Cb ond to HALD.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[14][15][16] It hasb een proven that tungsten and tungsten nitride are effective co-catalysts of Pt and Pd in hydrogen evolution reactiona nd oxygen reduction reaction. [15,17,18] Importantly,i no ur previous work it was found that Mo 2 Nc ould distinctively enhancet he activity and selectivity of Pt on the ternary Pt-Mo 2 N/SBA-15 catalystf or the hydrogenation of CAL at the C=Ob ond to COL. Thus, we were curious to investigate whether the synergistic effect between Pd and WN could promote the catalytic performance of Pd for the hydrogenationo fc innamaldehyde at the C=Cb ond to HALD.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, metal nitrides have been studied intensely owing to their synergistic effects and Pt‐like behavior in traditional catalysis and electrocatalysis . It has been proven that tungsten and tungsten nitride are effective co‐catalysts of Pt and Pd in hydrogen evolution reaction and oxygen reduction reaction . Importantly, in our previous work it was found that Mo 2 N could distinctively enhance the activity and selectivity of Pt on the ternary Pt–Mo 2 N/SBA‐15 catalyst for the hydrogenation of CAL at the C=O bond to COL.…”
Section: Introductionmentioning
confidence: 99%
“…Many new inorganic [8] or carbon-based catalyst composite materials [9,10] are under development, and in particular, synthetic methods based on the carbonisation of precursors to yield carbon-embedded catalysts [11,12] have proved beneficial. Novel and highly efficient types of carbon-embedded platinum catalysts have been obtained via carbonisation [13]. However, directly embedding active nanoplatinum catalysts without loss of activity during carbonisation in a one-step procedure is uncommon and desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition, the XPS spectrum of V 2p could be divided into three peaks at about 513.9 eV, 515.2 eV and 516.9 eV, corresponding to VÀ N, VÀ NÀ O as well as VÀ O, respectively. [39,40] These results disclosed the presence of VN, NC and a few VO x in the nanocomposite.…”
Section: Resultsmentioning
confidence: 69%
“…The peaks at 530.0 eV, 531.1 eV and 532.2 eV in the O 1s XPS spectrum originated from V−O, V−O‐N and O−C=O, respectively, and the presence of V−O, V−O−N was ascribed to the vanadium oxides on the surface of VN NPs . In addition, the XPS spectrum of V 2p could be divided into three peaks at about 513.9 eV, 515.2 eV and 516.9 eV, corresponding to V−N, V−N−O as well as V−O, respectively . These results disclosed the presence of VN, NC and a few VO x in the nanocomposite.…”
Section: Resultsmentioning
confidence: 99%